Theory Aside - Anne- Lise, François; Daniel, Stout; Elizabeth, A. Povinelli; Eve, Kosofsky Sedgwick; Frances, Ferguson; Heather, Love; Ian, Balfour; Irene, Tucker; Jason, Potts; Jordan, Alexander Stein; Karen, Beckman; Mark B. N., Hansen; et al. (Duke University Press, 2014)
Where can theory go now? Where other voices concern themselves with theory's life or death, the contributors to Theory Aside take up another possibility: that our theoretical prospects are better served worrying less about "what's next?" and more about "what else?" Instead of looking for the next big thing, the fourteen prominent thinkers in this volume take up lines of thought lost or overlooked during theory's canonization. They demonstrate that intellectual progress need not depend on the discovery of a new theorist or theory. Moving subtly through a diverse range of thinkers and topics-aesthetics, affect, animation and film studies, bibliography, cognitive science, globalization, phenomenology, poetics, political and postcolonial theory, race and identity, queer theory, and sociological reading practices-the contributors show that a more sustained, less apocalyptic attention to ideas might lead to a richer discussion of our intellectual landscapes and the place of the humanities and social sciences in it. In their turn away from the radically new, these essays reveal that what's fallen aside still surprises.Contributors. Ian Balfour, Karen Beckman, Pheng Cheah, Frances Ferguson, William Flesch, Anne-Lise François, Mark B. N. Hansen, Simon Jarvis, Heather Love, Natalie Melas, Jason Potts, Elizabeth A. Povinelli, Eve Kosofsky Sedgwick, Jordan Alexander Stein, Daniel Stout, Irene Tucker